Examining Vaping Policies in Substance Use Disorder Treatment Facilities - Orrin D. Ware; G. Rose Geiger; Tara G. Bautista; Michael H. Baca-Atlas (Tobacco Use Insights)
Background Unlike combustible cigarettes, vaping does not produce smoke, creating ambiguity around indoor vaping policies. Vaping policies in substance use disorder treatment facilities may directly impact how an individual engages with treatment. Objective To examine associated factors with vaping policies within substance use disorder treatment facilities in the United States. Design This cross-sectional study used data from the National Substance Use and Mental Health Services Survey to examine data from substance use disorder treatment facilities. Other data included the state percentage of adults who use e-cigarettes from the Behavioral Risk Factor Surveillance System, and state-level indoor e-cigarette restriction policies from the State Tobacco Activity Tracking and Evaluations System. Methods A total of N = 16 042 substance use disorder treatment facilities in 2022 were included. Factors that were examined include [a] state percentages of adults who vape, [b] state indoor vaping restrictions, [c] tobacco use screening in facilities, [d] smoking/tobacco education and counseling in facilities, [e] availability of nicotine pharmacotherapies in facilities, [f] facility smoking policies, [g] availability of outpatient or non-hospital residential treatment, and [h] availability of a treatment program specifically for adolescents or young adults. Facility vaping policies is the outcome variable in this study with three values: [a] vaping is restricted, [b] vaping in designated outdoor area(s), and [c] permissive vaping policies (anywhere outside, designated indoor areas, anywhere inside, anywhere without restriction). Results Vaping policies across all treatment facilities include 45.9% restricted vaping, 45.9% permitted vaping in designated outdoor area(s), and 8.2% had a permissive vaping policy. State-level percentage of adults who use e-cigarettes, state indoor e-cigarette restrictions, facility smoking policies, and services provided by facilities were associated with different vaping policies, ranging from restrictive to permissive policies. Conclusions Various vaping policies exist in substance use disorder treatment facilities. Different vaping policies may have varied impacts on individuals’ treatment goals.